RESULTS OF A CONTROLLED EVALUATION OF A HOSPICE RAPID RESPONSE COMMUNITY SERVICE FOR END OF LIFE CARE. Issue Volume 4: Issue (2014)Supplement 1 (1st March 2014) - Butler, Claire; Holdsworth, Laura; Gage, Heather; Coulton, Simon; King, Annette
Abstract : Background: When faced with a life-limiting condition, most people would prefer to die at home but more than half continue to die in hospital. A 2011 systematic review concluded that there is only moderate evidence to show that home-based end of life teams reduce the likelihood of dying in hospital, though observational and descriptive studies suggest that home-based care with the capacity to respond rapidly to crises may improve the likelihood of dying at home. Aims: The primary aim of the study was to assess the impact of a new rapid response service (in addition to usual hospice and community palliative care services) on patients dying in their preferred place of death (PPD). Secondary objectives were to evaluate carers' quality of life and the overall cost of providing end of life care. Methods: Intervention: Hands-on care provided by trained Healthcare Assistants available day and night at 4 hours notice to support patients dying at home. Design: Quasi-experimental, multi-centred, controlled evaluation with embedded cost analysis. Results: 953 patients died with a PPD recorded and 155 carers completed questionnaires. The number of people achieving their PPD was not statistically significantly different in the intervention and control groups (about 60%). Patients in the intervention group were more likely to wish to die at home and significantly more patients in the intervention group died at home. The carers of patients in the intervention group experienced more problems with their mental and emotional health than those in the control group. The rapid response service did not significantly add to the costs of providing end of life care in the intervention group compared to the control group. Conclusions: Access to the rapid response service did not significantly affect whether patients died where they preferred.